Graduate Entrepreneur, A New Dimension for Graduate Employability: A Case Study at USIM - Ummi Salwa Ahmad Bustamam; Siti Norfaza Abdul Halit (International Review of Management and Marketing, 2017)
Graduate entrepreneurs and entrepreneurial graduates (graduates with entrepreneurial attributes) are among two focal concerns of the Ministry of Higher Education of Malaysia. This is due to the increasing numbers of unemployed graduates in Malaysia. The study conducted by Centre of Students' Entrepreneurship Development of University Sains Islam Malaysia (USIM) is addressing on how the graduate entrepreneur could be a new dimension for graduate employability at higher institutions. This paper is also aimed to share USIM's best practices in intensifying efforts to encourage more students to actively participate in entrepreneurship activities as their career path upon graduation. This will ultimately contribute to more job creators instead of job seekers.